1995
DOI: 10.1021/bi00051a020
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Acetate Induces a Conformational Change in Escherichia coli Primase

Abstract: Primase from Escherichia coli is a single-stranded DNA-dependent RNA polymerase. As such, it requires magnesium to carry out catalysis. Limited tryptic digestion was used to probe the conformations of primase as a function of magnesium acetate concentration. In the absence of magnesium, trypsin cleaved primase at three sites. Magnesium acetate induced a conformational change such that one of these sites became inaccessible to trypsin digestion and a new site became trypsin accessible. The conformational change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…This is consistent with the detection of conformational changes in the primases in the presence of Mg 2+ (50).…”
Section: Structure Of the Toprim Domain And Its Function In Catalysissupporting
confidence: 91%
“…This is consistent with the detection of conformational changes in the primases in the presence of Mg 2+ (50).…”
Section: Structure Of the Toprim Domain And Its Function In Catalysissupporting
confidence: 91%
“…The observed NTP-binding site in Sa DnaG is formed by multiple highly-conserved residues, many of which have been demonstrated previously to be critical for catalysis (Fig S1/S2a, Table 2). For example, the invariant acidic amino acids that ligand the metal ions involved in nucleotide coordination have been shown to be critical for metal binding and priming activity in both E. coli DnaG and in the related phage protein, T7 gp4 (Godson et al, 2000,; Lee and Richardson, 2005; Rodina and Godson, 2006; Urlacher and Griep, 1995). The positively-charged amino acids that emerge from the basic ridge to contact the nucleotidyl triphosphate moiety likewise have been examined, and found to be important for primase function (Keck et al, 2000; Rodina and Godson, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The Mg 2ϩ -dependent specificity of primase binding may reflect the requirement of Mg 2ϩ for forming the specific conformation of primase when interacting with DNA template. It has been reported that Mg(OAc) 2 could induce a conformational change in primase that resulted in an altered pattern of protease cleavage (23). For E. coli RNA polymerase, which has similar properties as E. coli primase, it has also been found that Mg 2ϩ plays roles in transience of formation of RNA polymerase and P R promoter complexes (20), and the location of the Mg 2ϩ binding site was reported recently (28).…”
Section: Vol 178 1996 Interaction Of Primase With G4ori C -Ssb Compmentioning
confidence: 93%